Nucleolin Promotes Cisplatin Resistance in Cervical Cancer by the YB1-MDR1 Pathway. (22nd April 2021) - Ke, Jing; Gu, Chunming; Zhang, Heyan; Liu, Yang; Zhang, Wenhao; Rao, Huiling; Li, Shan; Wu, Fuyun
Abstract : Purpose. Cervical cancer is the fourth most common cancer in women worldwide and is the main cause of cancer-related deaths in women. Cisplatin (DDP) is one of the major chemotherapeutic drugs for cervical cancer patients. But, drug resistance limits the effectiveness of cancer therapy. Nucleolin (NCL) is a nucleocytoplasmic multifunctional protein involved in the development of cancer. It has been reported that NCL may be a potential target for modulation of drug resistance. However, the precise molecular mechanisms are poorly understood. Materials and Methods . Human cervical cancer Hela cells and their cisplatin-resistant cell line Hela/DDP were used in this study. The protein level of NCL in cervical cancer cells was measured by western blot analysis. Hela cells and Hela/DDP cells were transfected with NCL overexpression plasmid or NCL siRNA separately. MTT and EdU assay were performed to evaluate the cell viability and sensitivity to cisplatin. The drug efflux function of MDR1 protein was assessed by intracellular rhodamine-123 accumulation assay.The promoter activity of MDR1 was assessed by using a dual-luciferase reporter assay. Results . We found that the protein level of NCL was elevated in Hela/DDP cells. Overexpression of NCL increased cervical cancer cell proliferation and attenuated the sensitivity to cisplatin. Overexpression of NCL increased Multidrug resistance (MDR1) gene expression and drug efflux. Our results demonstrated that NCL was highly related with cisplatin resistance in cervical cancer. NCL played an important role in MDR1 gene transcription through regulation of the transcription factor YB1. Conclusion . Our findings revealed the novel role of NCL in cisplatin-resistant cervical cancer and NCL may be a potential therapeutic target for chemoresistance.